Operationalizing places in GIScience - Tang, Vicente (2021)
Tang, V., & Painho, M. (2021). Operationalizing places in GIScience: A review. Transactions in GIS, 25(3), 1127 - 1152. https://doi.org/10.1111/tgis.12767